(untitled) (Journal of Universal Science Research, 2025)
The article discusses the methodology of using the scaffolding model in the formation of English speaking competence of primary school students whose education is conducted in Uzbek. According to the author, the use of this model creates a stress-free environment in English lessons, which ensures the quality and effectiveness of education.